Memorable cultural tourism experience: blogger narrative analysis - Ari Sulistyanto; Saeful Mujab; Hamida Harahap (Universitas Merdeka Malang, 2022)
Cultural tourism has an important influence on the development of the tourism industry. The travel experience stories of bloggers written through blogs contributed to the initial introduction and impact of other travel planning tours. It can also be used as a reference by tourism agents. However, the travel experience stories of these bloggers have not been structured as themes and memorable experiences. Whereas the core product of the tourism business is a memorable experience. In the perspective of narrative paradigm theory (NPT), a story or narrative is successful as a human communication capable of forming meaning, if it has coherence and truth. . Therefore, this study aims to reveal the narrative structure told by bloggers. So that the meaning and theme of the cultural tourism experience can be understood as a memorable experience. This study uses a qualitative approach with narrative paradigm theory (NPT). The research data as the unit of analysis was collected from the narrative stories of bloggers published on weblogs. Meanwhile, the principle of the grounded theory approach is aimed at uncovering the narrative themes of bloggers. The results of the study explain the narrative of bloggers in cultural tourism that is told through blog pages as narrative rationales because there is coherence and truth so that they form meaning as a positive, enjoyable, and satisfying experience. The category of cultural tourism that bloggers often visit is the category of cultural heritage, such as museums, temple sites, and old buildings, as well as local or traditional villages. The results of this study also found that a series of blogger narratives formed the theme of memorable experiences through cultural tourism, such as spirituality, intellectual national identity, and local uniqueness. Overall this research reveals, the rational structure of the narrative in the blogger's narrative explains the meaning of an impressive experience in cultural tourism as a positive, pleasant, and memorable view that tourists remember after visiting a destination that is categorized as cultural tourism, retold in the form of a story.